Implementasi Internet of Things dalam Rantai Pasok UMKM Berbasis Digital - Adhi Susano (Yayasan Cendekia Gagayunan Indonesia, 2026)
The digital era has fundamentally changed the business landscape, including in the supply chain management of Micro, Small, and Medium Enterprises (MSMEs). This study analyzes the implementation of Internet of Things (IoT) technology in the digital-based supply chain of MSMEs in Indonesia. The research method used a qualitative approach with a case study of 50 MSMEs that have implemented IoT systems. Data were collected through structured interviews, field observations, and documentation analysis. The results show that IoT implementation can increase operational efficiency by up to 35%, reduce logistics costs by 28%, and improve inventory accuracy by up to 92%. However, the main obstacles include limited human resources, technological infrastructure, and investment capital. This study contributes to the development of MSME supply chain digitalization strategies in Indonesia.